Three scenarios for the Yemen war: Cease fire negotiations, North-South confrontation or division - Mareike Transfeld (Stiftung Wissenschaft und Politik (SWP), 2022)
The future of the Yemen conflict will be decided about 120 kilometres east of the capital Sanaa, in the city of Marib. So far, the internationally recognised Yemeni government, supported by Saudi Arabia, has been able to ward off a two-year offensive from the Houthi movement, which originates from the north of the country and is aiming to take hold of the eastern provincial capital. The Houthis have had the military advantage, but as of January 2022, are being pushed on the defensive by the United Arab Emirates (UAE)-backed Giants Brigade, which is advancing into the governorate of Marib from the south. Conceivable scenarios for the course of the conflict are: 1) ceasefire negotiations after a successful defence of Marib; 2) the fall of the provincial capital as the starting point of a shift of the conflict to the southern parts of the country; or 3) a negotiated division of the country with participation of the UAE and Iran. Against this backdrop, Germany and its European partners should support regional powers' attempts at rapprochement and begin discussing new political perspectives for the future of Yemen with civil society and parties to the conflict.
Keywords: 320